Climate-resilient crop varieties, productivity and household welfare: evidence from Nigeria - Amadu Yaya Kamara; Oyakhilomen Oyinbo; Oluwole, Temitope S.; Jajua, Mohamed; Kamai, Nkeki (Springer, 2025)
Climate shocks pose significant threats to socioeconomic development, especially in agrarian areas where farmers, particularly women, are highly vulnerable to the negative consequences of climate variability. Women in these regions often face greater challenges due to limited access to resources, information, and agricultural inputs, which can exacerbate the impacts of climate change on their productivity and welfare. In response to these challenges, climate-resilient improved crop varieties have been disseminated to farmers over the years in a specific region in Nigeria. However, the productivity and welfare impact of these varieties, particularly in relation to gender differential outcomes, remains an empirical question. This paper examines the drivers and impacts of the adoption of climate-resilient cowpea varieties (CRCVs), with a focus on gender, using endogenous and exogenous switching regression models. Results show that the adoption rate of climate-resilient cowpea varieties is about 58% in the study area. Among other factors, the education of farmers and agricultural extension services strongly explain the adoption of these varieties. Notably, the adoption of CRCVs significantly increased yield, food expenditure, and non-food expenditure among adopters. While there is a slightly higher adoption rate among male-headed households, the results indicate no substantial gender differences in yield, food expenditure, and non-food expenditure between male- and female-headed households that can be attributed to returns or level effects.